Original paperSTRATEGY OF VISUAL PROPRIOCEPTIVE CONTROL IN PATIENTS WITH INJURY TO THE ANTERIOR CRUCIATE LIGAMENT OF THE KNEE AND HEALTHY INDIVIDUALS (SOCCER PLAYERS) - Piontek, T.; Ciemniewska-Gorzela, K.; Szulc, A.; Dudziński, W. (Biology of Sport, 2012)
Objective: Knee joint dysfunction resulting from injury to the anterior crucial ligament (ACL) is associated not only with mechanical joint instability but also with damage of ligamentous receptors responsible for the joint proprioception. It was found that disturbances of signals from the damaged joint produce disorders in movement perception and position of the analogous joint in the normal limb. This study is aimed at evaluating the control strategy in patients with an injury to the anterior crucial ligament.Design: Cohort study; Level of evidence, 3. Subjects/Patients- 84 men, aged 15 to 55 years (mean age 27 years) were included in this study. Methods- Patients were divided into two groups: those with unilateral injury to the ACL (33 patients) and a control group of healthy volunteers (soccer players; 51 men). Anterior crucial ligament damage was confirmed with arthroscopic knee joint examination in every patient. The way of visual proprioceptive control was assessed with both dynamic (DRT) and static (SRT) Riva tests standing on one leg. Tests were performed with the Delos Postural Proprioceptive System (Delos s.r.l., Corso Lecce, Torino, Italy) in the biomechanical evaluation laboratory at Rehasport Clinic in Poznań. Results: A statistically significant difference for deviations from the averaged axis in SRT (static Riva test) with closed eyes was found between the limb with a damaged ACL and the normal limb in the group of patients with injury to the ACL (p=0.006) and between the limb with a damaged ACL and normal limbs in healthy volunteers (p=0.022). A statistically significant difference for deviations from the averaged axis in SRT with closed eyes was also found between the dominant and non-dominant limb in healthy volunteers (p=0.013). No significant differences in the results of tests with open eyes were noted. Conclusions: The results of systems and their contribution to the visual proprioceptive control suggest an important role of the visual system in compensation of archeproprioceptive system disorders resulting from injury to the ACL. Clinical Relevance: Neurological deficits of proprioceptive perception, associated with injury to the ACL and affecting the balance, may be noted only in the results of tests performed with closed eyes.